Infrastructure and performance evaluation of Integrated Child Development Service Scheme in selected areas of Mysore, Karnataka, India - Siddalingappa, Hugara; Hoogar, Varsha; M., Renuka (International Journal Of Community Medicine And Public Health, 2016)
Background: Integrated child development scheme is a flagship program in the field of nutritional services in India. Even after decades of its launch, there are some lacunae in infrastructure, manpower, work hours, facility provision for the children. In spite of continuous innovations and changes under nutrition and growth retardation is still a problem. The objectives of the studies were to assess the infrastructure and facilities at the Anganwadi (AW) centres in the field practice area of a private Medical College in Mysore and to assess the growth pattern of the children in these Anganwadis. Methods: All the Anganwadis in the villages under two rural field practice areas of a medical college were surveyed using a pre-tested questionnaire. Details regarding the infrastructure, materials available and work details were collected by visiting the Anganwadi and interviewing the Anganwadi worker (AWW). Anthropometric measurements of the children were recorded. Results: In two primary health centres (PHC) and one urban health centre (UHC), 43 Anganwadi centres were surveyed, covering 585 children. Separate kitchen and toilet was present in 88.4 and 90.7% of AW respectively. In 22 (51%) centres children were sitting on the floor. All centers had helpers but one centre was not appointed with AWW. Mean years of experience was 18.9±6.7. There were 270 boys (46.2%) and 315 girls from two to six years of age. Mid upper arm circumference was less than 13.5cm in 63 (10.8%) children. Conclusions: Most of the Anganwadis were given the basic facilities and functioning optimally. Still there are some shortcomings in infrastructure and physical growth of the children.